(untitled) (Research, Society and Development, 2022)
Vegetables oils are renewables sources of ready availability with vast commercial employability. The application of these oils, generally, requires refining procedures for the removal of substances that make it unfeasible, such as phosphatides, proteins and free fatty acids. The objective of this study was to evaluate the effect of acid and aqueous degumming on the physical-chemical properties of crude oil of Mauritia flexuosa L.f. (buriti), palm tree of the family Arecaceae, very commercially exploited and well adapted to the Cerrado biome. Physical and chemical analysis were performed as acidity index, peroxide index, refraction, viscosity, density, gas chromatography coupled to the mass spectrometer and infrared spectroscopy before and after the refining process. The acidity, density and refraction indices didn´t change significantly during the treatments; however, significant differences were observed for the peroxide and viscosity parameters after the acid degumming process. Chromatographic and infrared spectroscopy results didn´t reveal changes in the constitution of constituent esters. The acid degumming was more efficient for the removal of undesirable substances, with significant variation (p < 0.05) for the peroxide index after this process. However, M. flexuosa oil presented good stability, keeping indexes acceptable in view of the current resolutions for its use.